2018
DOI: 10.1200/jgo.17.00071
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Parotid Non-Hodgkin Lymphoma: A Meta-Analysis

Abstract: PurposeThis meta-analysis aimed to review the published outcomes of parotid non-Hodgkin lymphoma (NHL) pertaining to different treatment modalities.Materials and MethodsA total of 48 journal articles published between 1993 and 2015, comprising 742 cases of parotid NHL, were initially evaluated. In total, 108 patients from 12 studies who had sufficient data for analysis, including age, tumor histopathology, treatment modality, and outcome at final follow-up, were included. Patients were randomly assigned to dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 49 publications
0
9
0
1
Order By: Relevance
“…The studies have suggested that in lowstage MALT lymphoma of the parotid, chemotherapy alone results in similar outcomes to those of radiation therapy alone. However, in more aggressive subtypes such as diffuse large B-cell lymphoma, a combination of chemotherapy and radiation therapy is usually recommended [18]. Our case offers a clear example of a patient for whom radiological studies, considered in the context of her past medical history, and confirmed by pathologic analysis, avoided unnecessary surgery in the management of her parotid gland neoplasm.…”
Section: Discussionmentioning
confidence: 90%
“…The studies have suggested that in lowstage MALT lymphoma of the parotid, chemotherapy alone results in similar outcomes to those of radiation therapy alone. However, in more aggressive subtypes such as diffuse large B-cell lymphoma, a combination of chemotherapy and radiation therapy is usually recommended [18]. Our case offers a clear example of a patient for whom radiological studies, considered in the context of her past medical history, and confirmed by pathologic analysis, avoided unnecessary surgery in the management of her parotid gland neoplasm.…”
Section: Discussionmentioning
confidence: 90%
“…6 However, with the large number of cases in this present study, the distribution of lymphoma subtypes resembles the distributions reported in the orbit and OA rather than that of the salivary glands. 4,[11][12][13][14][15] The distribution of lymphoma subtypes differed between eye cancer centers. The center in Hyderabad had a markedly higher proportion of patients with EMZL (84%) than the remaining eye cancer centers (43%-61 %), while the Copenhagen Center, which is a national eye cancer center, had a noticeably high proportion of MCL (23%) (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Only 22 cases reported stage at diagnosis, with 21 cases at initial stages (I/II). Advanced stages represented 4.5% ( Table 1 ) , which is lower than in major salivary glands, where 23% of cases were previously diagnosed in stages III or IV 28 …”
Section: Introductionmentioning
confidence: 87%